2020
DOI: 10.1073/pnas.1916825117
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A and B viruses with reduced baloxavir susceptibility display attenuated in vitro fitness but retain ferret transmissibility

Abstract: Baloxavir marboxil (BXM) was approved in 2018 for treating influenza A and B virus infections. It is a first-in-class inhibitor targeting the endonuclease activity of the virus polymerase acidic (PA) protein. Clinical trial data revealed that PA amino acid substitutions at residue 38 (I38T/F/M) reduced BXM potency and caused virus rebound in treated patients, although the fitness characteristics of the mutant viruses were not fully defined. To determine the fitness impact of the I38T/F/M substitutions, we gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 43 publications
(97 reference statements)
6
45
0
Order By: Relevance
“…Furthermore, a recombinant I38T-variant A/H1N1pdm09 virus demonstrated similar fitness characteristics in ferrets to the patient-derived A/H1N1pdm09 isolate, suggesting that transmission of the variant by respiratory droplets/aerosols was restricted to a greater extent than transmission by direct contact. Our study revealed that populations of I38T-variants are outcompeted by WT viruses in both A/H1N1pdm09 and A/H3N2; however, pure populations of I38T-variant viruses were still able to be transmitted in ferrets in accordance with previous studies (Imai et al, 2019; Jones et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, a recombinant I38T-variant A/H1N1pdm09 virus demonstrated similar fitness characteristics in ferrets to the patient-derived A/H1N1pdm09 isolate, suggesting that transmission of the variant by respiratory droplets/aerosols was restricted to a greater extent than transmission by direct contact. Our study revealed that populations of I38T-variants are outcompeted by WT viruses in both A/H1N1pdm09 and A/H3N2; however, pure populations of I38T-variant viruses were still able to be transmitted in ferrets in accordance with previous studies (Imai et al, 2019; Jones et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In existing studies investigating the fitness of PA/I38T-substituted influenza viruses in animal models, variant influenza viruses of recombinant and patient-derived origins have been capable of robust viral replication in mice, hamsters and ferrets (Checkmahomed et al, 2019; Chesnokov et al, 2019; Imai et al, 2019; Jones et al, 2020). Ferrets represent the gold standard transmission model for evaluating the fitness of influenza viruses (Belser, Eckert, Tumpey, & Maines, 2016); of the available reports, patient-derived and recombinant I38T viruses have previously been shown to transmit from experimentally inoculated DFs to naïve recipients by direct (Jones et al, 2020) and airborne contact (Imai et al, 2019; Jones et al, 2020) routes. In our study, patient-derived A/H3N2 and A/H1N1pdm09 I38T-variants, when evaluated as pure viral populations, could sustain a chain of three sequential generations of direct contact transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, these substitutions were unable to restore the growth impairment of the I38T-substituted viruses. Given that I38-substituted viruses show different patterns in terms of replicative capacity dependent on the type/subtype or isolated year, 11,19,26,28…”
Section: Discussionmentioning
confidence: 99%
“…However, virus specimen from a baloxavir-treated patient was reported to contain I38K as a mixture (I38 T/K/I) in Japan during 2018–19 season ( Takashita et al, 2019a ). Recently Jones and colleagues have shown that introduction of polar, positively charged lysine (K) at PA-38 reduced the polymerase activity by 50% compared to wildtype (I38) in minireplicon assay ( Jones et al, 2020 ). However, they apparently did not investigate the effect of this amino acid substitution on virus properties.…”
Section: Discussionmentioning
confidence: 99%
“…Virological surveillance conducted in Japan during 2018–19 season detected viruses carrying PA-38 substitutions with frequency of 2.3% in A(H1N1)pdm09 and 8.0% in A(H3N2) viruses, while no I38-substituted influenza B virus was reported ( https://www.niid.go.jp/niid/images/flu/resistance/20191227/dr18-19e20191227-1.pdf ). In ferret transmissibility experiments, influenza A and B viruses carrying I38T and I38M were shown to efficiently transmit to naïve ferrets by direct contact and airborne routes ( Imai et al, 2020 ; Jones et al, 2020 ). Moreover, limited human-to-human transmission of I38T-carrying influenza A viruses have been documented, raising public health concerns ( Imai et al, 2020 ; Takashita et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%